Gravidez na adolescência e sua prevenção: sentidos atribuídos por um grupo de adolescentes escolares de Porto Velho – Rondônia - Fernandes, Daiana Evangelista Rodrigues (2019)
Recent World Health Organization data show that approximately 16 million girls aged 15-19 each year and 1 million girls under 15 annually become mothers worldwide. Teenage pregnancy is an important public health problem that can affect the mother-child binomial in social, biological and psychological aspects. The aim of this study is to identify and analyze the meanings attributed by school adolescents to teenage pregnancy and its prevention. Qualitative study, approaching the principles of ethnography, conducted in a public school in the city of Porto Velho - RO, from October 2017 to November 2018. Participants were 20 adolescents of both sexes, aged 16 or 17 years. who had sexually active lives or not and were in the first or second year of high school. Data were obtained during the fieldwork, through participant observation and individual interviews, following a semi-structured script. The interviews were analyzed by the meanings interpretation method. From the process of analysis of the qualitative material obtained two themes emerged. The first, “Information for the prevention of teenage pregnancy”, shows that mothers are the people who talk and report the most about aspects related to their children's sexual health. Participants also reported as sources of information, leaflets, lectures, classes at school, advertisements and television programs. Regarding contraceptive methods, they reported mainly condom use and oral contraception. The theme “Repercussions of teenage pregnancy” shows that, in general, adolescents consider pregnancy at this stage of life something wrong, which undermines their studies and imposes the need to work. In addition, they evidenced the desire to complete their studies and develop in various professions in order to obtain financial stability and material goods so that only then can they have children. The study showed that participants referred more about their plans and dreams for development as people and future professionals than the desire for a teenage pregnancy. In contrast, the process of sexual and reproductive health education for these adolescents was weakened. Information is fragmented and there is no necessary dialogue between family, school and health service, and others who could participate in this continuum of actions for health promotion. Similarly, the use of contraceptive methods was not stable. However, participants demonstrated the use of the information to which they had access and adopted contraceptive measures motivated by future desires and dreams.